Spatial Distribution of Dengue Hemorrhagic Fever Cases in the Temindung Primary Health Care Area, Samarinda City, 2024: A Nearest Neighbour Analysis - Fitrah, Muhammad Aidil; Saefurrohim, Muhamad Zakki (Fakultas Kedokteran, 2025)
The total number of dengue cases reported nationally has reached 88,593, resulting in 621 deaths in 456 districts/cities in 34 provinces. Temindung Health Center is the health center with the highest cases in Samarinda City in 2023. This study aims to analyze the distribution of DHF cases in the working area of Temindung Health Center in Samarinda City. This study uses the Nearest Neighbour Analysis method to analyze the spatial pattern of the distribution of DHF cases and shows that the distribution of cases does not occur randomly which is complemented by the buffer analysis method to identify risk areas based on geographical proximity to the Puskesmas of DHF cases in January-September 2024. The results showed that there were 71 cases of DHF in the working area of Temindung Health Center, where the peak of cases occurred in January with 19 cases. The results of Nearest Neighbor Analysis showed a nearest neighbor index value of 0.648 and a Z-score of -5.67, which indicated that the distribution pattern of DHF cases was very clustered, the results of the buffer analysis showed that the distribution of cases occurred mostly around the 500 meter zone from the Puskesmas. DHF prevention and control efforts should focus on areas with high case cluster patterns, especially around densely populated zones and far from access to health facilities, by strengthening active surveillance and risk area-based interventions.